2004
DOI: 10.1074/jbc.m404485200
|View full text |Cite
|
Sign up to set email alerts
|

“Catch 222,” the Effects of Symmetry on Ligand Binding and Catalysis in R67 Dihydrofolate Reductase as Determined by Mutations at Tyr-69

Abstract: R67 dihydrofolate reductase (R67 DHFR)To understand the interactions between specific Tyr-69 residues and each ligand, asymmetric Y69F mutants were generated that contain one to four Y69F mutations. A general trend observed from isothermal titration calorimetry and steady-state kinetic studies of these asymmetric mutants is that increasing the number of Y69F mutations results in an increase in the K d and K m values. In addition, a comparison of steady-state kinetic values suggests that two Tyr-69 residues in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The first asymmetric mutation studied was Q67H (6). This study focuses on the role of Lys-32 residues, and a third study considers the effect of Y69F mutations (see companion paper: Stinnett et al (46)). …”
Section: R67 Dihydrofolate Reductase (R67 Dhfr)mentioning
confidence: 99%
“…The first asymmetric mutation studied was Q67H (6). This study focuses on the role of Lys-32 residues, and a third study considers the effect of Y69F mutations (see companion paper: Stinnett et al (46)). …”
Section: R67 Dihydrofolate Reductase (R67 Dhfr)mentioning
confidence: 99%
“…However, using osmotic pressure, we could titrate the ability of DH5␣ carrying a Y69L R67 DHFR clone to confer resistance to TMP. The Y69L mutant enzyme has levels of activity intermediate between those of the R67 DHFR and the K32M mutant (9,33). This pattern of behavior indicates a window of enzyme activity that allows cell growth and selection by osmotic stress.…”
Section: Resultsmentioning
confidence: 95%
“…The mobility of the tail regions has been observed not only in both X-ray crystallography and NMR studies but is also in agreement with mutational analysis. Asymmetric mutations of Y69 indicate that variable positions of the pABA-Glu tail of DHF are tolerated [26], and studies of K32 showed that two mutations on different half pores produce topologies that allow comparable interactions between K32 and the Glu tail of DHF [20]. Furthermore, mutations at the centre of the pore (Q67H) are accompanied by inhibition of the catalytic activity due to non-productive binding [70], while mutations close to the pore surface (K32M and Y69F) are not.…”
Section: Multiple Conformationsmentioning
confidence: 99%
“…molecular dynamics, MD). Many new experimental studies have been conducted on R67 DHFR since the publication of this initial study [17,19,20,[25][26][27], providing new insights into the mechanism R67 DHFR uses to catalyse the reaction. Some of this new data, such as the interaction between the hydroxyl group of Y69 and NADPH observed in mutational analysis [25], is not in agreement with the previous docking results [21] and, therefore, this model requires re-examination.…”
Section: Introductionmentioning
confidence: 98%